PERBANDINGAN HASIL BELAJAR KIMIA SISWA MENGGUNAKAN KARTU TRUTH AND DARE DENGAN PEMBELAJARAN KONVENSIONAL - Tiara Nitaria Sinaga; Nurhamidah Nurhamidah; Dewi Handayani (University of Bengkulu, 2022)
This study aims to find out how the student's chemistry learning outcomes on the periodic properties of elements in two grade X Mathematics and Natural Sciences at SMA Negeri 02 Mukomuko with the media card game Truth and Dare. The type of research used is a quasi-experimental study with a population of class X MIPA at SMAN 2 Mukomuko and the sample is class X MIPA 2 and class X MIPA 3. The sample in this study is class X Mathematics and Natural Sciences 3 as a control with conventional learning and class X Mathematics 2 as a control. experiment using truth and dare media. Analysis of the data used is the average value of posttest, normality test, homogeneity test, and t test. Data on student learning outcomes were obtained from the pretest and posttest scores with an average of 39.36 and 47.74 for the control class while the experimental class was 26.67 and 68. Then a t-test was carried out with a significant level (? = 0.05), then the value of t-count is 3.290 and t-table is 1.7084. The results showed that there were significant differences in learning outcomes between classes that used Truth and Dare card media and classes that did not use Truth and Dare card media.